2020
DOI: 10.3390/buildings10030041
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glass Compounds in Autoclaved Bricks

Abstract: This study describes the relationship between the physio-mechanical and chemical properties of sand-lime materials which have undergone hydrothermal treatment, and which were modified through the introduction of glass components (90% glass sand, GS). Process parameters such as temperature, pressure and saturation vapor pressure were found to have a significant impact on the series of chemical reactions as well as on the formation and transformation of solid hydrates. During the stirring process of sand-lime ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…In the GG sample, the synthesis products were formed in the spaces between and on the surface of the glass aggregate; however, they are much less dense/packed and reveal a lower crystallisation degree. The products formed in the studied samples resemble hydrated calcium silicates typical of the standard sand-lime products [44]. Based on the microstructure observation, it can be concluded that their development degree varies according to the waste glass colour used.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In the GG sample, the synthesis products were formed in the spaces between and on the surface of the glass aggregate; however, they are much less dense/packed and reveal a lower crystallisation degree. The products formed in the studied samples resemble hydrated calcium silicates typical of the standard sand-lime products [44]. Based on the microstructure observation, it can be concluded that their development degree varies according to the waste glass colour used.…”
Section: Resultsmentioning
confidence: 69%
“…The compressive strength of the WG samples was 11.1% higher than that of the GG samples. The use of waste glass as a substitute for quartz sand was also found to have improved the compressive strength in the study of Stępie ń and all [44]. The hydration temperature of lime with the increasing share of WG was lowered, hence it can be deducted that hydration of lime during the production of autoclaved samples provided adequate chemical bonds, and as a result strength of samples increased.…”
Section: Resultsmentioning
confidence: 87%
“…Due to its basic feature, which is the ability to generalize knowledge for new, previously unknown data, NNs are widely used in various scientific and engineering fields. Comprehensive reviews of the use of NNs in civil engineering have been presented in the literature, e.g., see [33][34][35][36][37][38]. In addition, networks can be formulated to analyze different regression problems by providing input/output data according to Paez's classification [39].…”
Section: The Application Of Nn To Analyze Regression and Identificati...mentioning
confidence: 99%
“…However, recycled products [ 20 , 21 ], polypropylene mesh [ 22 ], other production wastes and leachate from landfills [ 23 , 24 ] were also taken into account. The newest research on the sand-lime products is also based on their modification with waste glass in the form of glass sand and glass cullet [ 25 , 26 , 27 ]. Similarly to cement composites, these studies have shown that the increase in the amount of glass sand contributes to the higher compressive strength of these products, while the bulk density and water absorption of these samples is lower [ 25 , 26 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The newest research on the sand-lime products is also based on their modification with waste glass in the form of glass sand and glass cullet [ 25 , 26 , 27 ]. Similarly to cement composites, these studies have shown that the increase in the amount of glass sand contributes to the higher compressive strength of these products, while the bulk density and water absorption of these samples is lower [ 25 , 26 , 28 ]. These tests completely described the changes in the microstructure resulting from the modifications to the composition of the initial mixture.…”
Section: Introductionmentioning
confidence: 99%